2010
DOI: 10.1038/onc.2010.416
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR-21 by Ras in vivo and its role in tumor growth

Abstract: miR-21 is a microRNA (miRNA) frequently overexpressed in human cancers. Here we show that miR-21 is upregulated both in vitro and in vivo by oncogenic Ras, thus linking this miRNA to one of the most frequently activated oncogenes in human cancers. Ras regulation of miR-21 occurs with a delayed kinetic and requires at least two Ras downstream pathways. A screen of human thyroid cancers and non-small-cell lung cancers for the expression of miR-21 reveals that it is overexpressed mainly in anaplastic thyroid carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 33 publications
3
101
0
4
Order By: Relevance
“…[15][16][17] Whereas miR-34 transcriptionally controls p53 to downregulate a set of genes involved in cycling tumor cells, 18 oncogene Ras-mediated induction of miR-21 was attributed to Ras-dependent tumor cell proliferation by controlling gene expression of cell cycle checkpoint regulators. 19 More recent studies have determined the role of miRs in stem cell proliferation and reported that miRs relevant to cell cycle progression in embryonic stem cells included miR-290 cluster which suppressed process of epithelial mucosa, [29][30][31] thus suggesting that miR-143 may promote different cellular functions based upon lineage background as well as differences in the genetic make-up of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Whereas miR-34 transcriptionally controls p53 to downregulate a set of genes involved in cycling tumor cells, 18 oncogene Ras-mediated induction of miR-21 was attributed to Ras-dependent tumor cell proliferation by controlling gene expression of cell cycle checkpoint regulators. 19 More recent studies have determined the role of miRs in stem cell proliferation and reported that miRs relevant to cell cycle progression in embryonic stem cells included miR-290 cluster which suppressed process of epithelial mucosa, [29][30][31] thus suggesting that miR-143 may promote different cellular functions based upon lineage background as well as differences in the genetic make-up of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…miR-21 is up-regulated by RAS in vitro and in vivo and is frequently overexpressed in human cancers. LNA directed against miR-21 reduced tumor growth in vivo [110] , which suggests a therapeutic role for anti-miR-21 in treating cancers. In addition, miR-16, which is frequently deleted and/ or down-regulated in human cancers, significantly inhibits prostate tumor growth in vivo when delivered by atelocollagen via tail vein injection [111] .…”
Section: Implications Of Cell Cycle-related Mirnas In Anti-cancer Thementioning
confidence: 92%
“…miR-146a was identified as a common target of Krüppel-like factor 8 (KLF8) and TGFb, both of which are known EMT-inducers in breast cancer cell line (Wang et al 2013). miR-21 was upregulated in human ATC cell lines (Mitomo et al 2008) by oncogenic Ras (Frezzetti et al 2011). PTCs with high expression of miR-21 had significantly poorer disease-free survival rates and higher LN metastasis by in situ hybridization .…”
Section: Downregulation Of Specific Micrornasmentioning
confidence: 97%